Pengendalian kualitas pakcoy pada PT. Sayuran Pagi dengan menggunakan metode six sigma - Bagas Elang Samudra; Ina Siti Hasanah (Agroindustrial Technology, University of Trunojoyo Madura, 2026)
Vegetables are agricultural products that are perishable (easily damaged), so they are susceptible to a decrease in product quality. One of the efforts to improve the quality of vegetable products is to control the quality of these products. The purpose of this study was to determine the disabled group, the factors that cause the disability and alternative efforts that can be implemented in pakcoy vegetables. This study uses the Six Sigma method to improve the stage. This research was conducted from May to July 2023 at PT. Morning vegetables. The results showed that PT Sayuran Pagi was still in the 3-sigma range with a DPMO value of 35438.48. The defect groups of pak choi vegetables at PT. Sayuran Pagi consists of 3 (three) defect groups, namely broken stems of 77.56%, yellow leaves of 17.16% and white spots of 5.28%. Factors that cause defects in morning vegetables are human factors, methods, machines and the environment. Alternative efforts that can be implemented include: Monitoring and guiding during harvesting, making checklists for checking nutrition, calibrating TDS tools regularly, providing information on the importance of closing doors, making reminder boards in front of green house doors, implement personal hygiene SOPs, provide counseling about pests and diseases that have the potential to attack pakcoy vegetables, provide direction to partners regarding distribution, use sturdy containers, create SOPs on nutrition for pakcoy vegetables, change plant spacing between holes, carry out preventive pest and disease control with natural pesticides.